2017
DOI: 10.5539/elt.v10n5p158
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Brain-Based Teaching on Young EFL Learners’ Self-Efficacy

Abstract: The present study aimed to investigate the effect of brain-based teaching on the self-efficacy of young EFL learners. The initial participants of the study were 90 learners within the age range of 13-16 who were selected based on convenience sampling. Theses 90 young EFL learners were given a Flyers test the scores of which were used to choose 60 homogeneous learners whose scores fell within the range of +/-one standard deviation from the mean. The 60 selected learners were then divided into an experimental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Furthermore, the findings of the preset study indicate that BBL has a huge effect size on developing the participants' intrinsic motivation. These results are in line with the findings of previous studies such as (Degan, 2011;Brumen, 2011;Oghyanous, 2017) which assured that BBL had a positive impact on developing learners' intrinsic motivation.…”
Section: Discussion Of Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the findings of the preset study indicate that BBL has a huge effect size on developing the participants' intrinsic motivation. These results are in line with the findings of previous studies such as (Degan, 2011;Brumen, 2011;Oghyanous, 2017) which assured that BBL had a positive impact on developing learners' intrinsic motivation.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…Finally, the results of the preset study are consistent with the results of some previous research such as (Ali, 2017;Carreira, 2012;Ibrahim, 2019;Kim, 2011;Kitjaroonchai and Kitjaroonchai, 2012;Jutarat, 2016;Morib and Gobe, 2006;Wang, 2008;Wimolmas, 2012;Muftah and Shameem, 2013;Mohammed, 2015) which confirmed that motivation plays a very vital role in developing EFL skills. Moreover, the results of the preset study support previous studies which assured the positive impact of BBL on developing motivation to learn English such as (Bas, 2010;Brumen, 2011;Oghyanous, 2017;Safein, 2017). Furthermore, the findings of the preset study indicate that BBL has a huge effect size on developing the participants' intrinsic motivation.…”
Section: Discussion Of Resultssupporting
confidence: 82%
“…The same rise was also significant in a study assessing the effect of an intervention on self-regulated learning; the intervention was found to have a beneficial effect on strategy use and performance (Lu et al, 2017). Kassem (2019), Oghyanous (2017), and Namaziandost and Çakmak (2020) conducted studies with the same goal of increasing learners' efficacy but with a focus on teaching methods. Namaziandost and Çakmak (2020) used a flipped classroom approach; Kassem (2019) used a student-centered approach; and Oghyanous (2017) used brain-based teaching.…”
Section: Experimental Research: Raising Learners' Self-efficacy Beliefsmentioning
confidence: 81%
“…There were many previous studies which applied brain-based learning in the English as foreign language classroom. Oghyanous (2017) found that the effect of brain-based teaching approach toward self-efficacy of EFL students in Iran was significant. Brain-based learning was also proven to be effective in developing listening skills of the students and consolidating the recalling and the retention of the students' vocabulary as well as maximizing the motivation of the students in learning the skills of language (Salem, 2017).…”
Section: Introductionmentioning
confidence: 96%